The Leadership Task Model - Christoph Desjardins; Mark Baker (Journal of Applied Leadership and Management, 2013)
What are the most relevant leadership tasks that drive leadership productivity? Which levels of leadership tasks exist?
Keywords: 650; Leadership Task Model; leadership tasks; Me-Level; Self-Transparency; Relationship-Transparency; Morale Values and Inclusive Decisions; Us-Level; Strategy Definition; Culture Creation; Change Management; Interface- and Conflict Management